2017
DOI: 10.1245/s10434-016-5758-2
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on the Consensus Statement of the American Society of Breast Surgeons on Contralateral Prophylactic Mastectomy

Abstract: The increasing rate of contralateral prophylactic mastectomy (CPM) led the American Society of Breast Surgeons (ASBrS) to issue an evidence-based consensus statement on CPM, as well as a discussion guide that health care providers can use to facilitate shared decision making with patients considering CPM for unilateral breast cancer. This article suggests several ways to improve the discussion guide by eliciting patient values and preferences and by providing more current, detailed, and balanced information ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Some studies identified women’s reasons for choosing CPM and then, based on those reasons, argued that the procedure is a reasonable treatment choice for average-risk women. See, for example, Han et al (2011) and . Importantly, though, these instances truly are exceptions, and, further, they appear to have had little impact insofar as their arguments are not generally picked up and cited in other studies.…”
mentioning
confidence: 98%
“…Some studies identified women’s reasons for choosing CPM and then, based on those reasons, argued that the procedure is a reasonable treatment choice for average-risk women. See, for example, Han et al (2011) and . Importantly, though, these instances truly are exceptions, and, further, they appear to have had little impact insofar as their arguments are not generally picked up and cited in other studies.…”
mentioning
confidence: 98%